Energy and Exergy Analyses of Heat Pump Cycle with Refrigerant Injection Technology - Abdul Hadi N. Khalifa; Johain J. Faraj; Hayder K. Hasan (Journal of Engineering, 2016)
The effect of refrigerant injection techniques on the performance of heat pump system based on exergy analysis was studied theoretically. Three refrigerant injection techniques were used; the first was achieved by injected vapour in volume ratios from 1 to 7% in the accumulator. The second was injection liquid refrigerant in the discharge line with the aid of Liquid Pressure Amplification (LPA) pump, with volume ratios from 1 to 10%. The third was a hybrid injection with volume ratios of injected vapour and liquid varied from 1 to 3% and 1 to 10%; respectively. The following improvements in cycle performance were observed. For vapour injection technique, the best ratio of injection was 5%, the exergy destruction reduced by 21% and exergy efficiency enhanced by 14.6%. For liquid injection technique the best ratio of injection was 6%, the reduction in exergy destruction was 34% while the exergy efficiency increased by about 21.4%. The hybrid injection technique increased the exergy efficiency by 23% when the volume ratio of vapour and liquid injections are 3% each. The effect of condensing pressure on the cycle performance was studied also. The optimum exergy efficiency of the cycle was 54.55% achieved when the condensing pressure was 15 bars.